Pesantren: Pendidikan Khas Indonesia, Tangguh di Masa Pandemi Covid-19 - Taufikin Taufikin (Tarbawiyah Jurnal Ilmiah Pendidikan, 2021)
Presented in this field research was conducted qualitatively explorative to answer important problems related to why pesantren in Indonesia feel comfortable and enjoy face-to-face alignment in the Covid-19 pandemic. The samples were taken at 11 pesantren in central and East Java that organized face-to-face learning. The data collected through interviews, observations, and documentation are then analyzed through Interpretative Phenomenology Analysis (IPA) using john dewey's theory of progressivism analysis. The results showed that pesantren still exists as an Islamic educational institution in the midst of a pandemic because 1) the tradition of the value of blessings, the strong value of blessings from ulama figures, Kiai, Ustaz can only be obtained when students interact directly (face-to-face) being the first factor why face-to-face learning is still implemented, 2) Pesantren is open and adaptive to follow the development of the covid-19 situation, Applying strict health protocols, quarantine santri when returning to pesantren, then close the pesantren environment from outside influences including santri guardians up to the safe situation and get permission from the covid-19 task force. 3) Utilization of information and communication technology, use of social media Facebook, WhatsApp, and pesantren website to provide information to stakeholders that pesantren is safe and comfortable for face-to-face learning. 4) Stakeholder synergy, demonstrated by the cooperation of parents, communities, and governments in understanding the role of pesantren as a safe institution for face-to-face learning. Referring to the results of this study, strengthening the existence of pesantren and stakeholders in the world of education, especially in Indonesia in implementing face-to-face learning in the era of the covid-19 pandemic, along with the readiness of the world of education towards the era of society 5.0.